Complexation copper(II) or magnesium ions with d-glucuronic acid – potentiometric, spectral and theoretical studies. Issue 14 (17th July 2016) - Jastrzab, Renata; Nowak, Martyna; Skrobanska, Monika; Zabiszak, Michał
Abstract: Results of potentiometric and spectral studies have shown that ind -glucuronic acid (GluA) with Cu 2+ or Mg 2+ systems, the complexes ML and ML(OH)x are formed. Overall stability constants (log β ) and equilibrium constants (log K e ) were calculated for all complex forms. The mode of coordination for each form was concluded on the basis of spectral values, Vis, EPR, and chemical shifts in the 13 C NMR. According to spectral analysis, Cu(GluA) exists in two possible forms, which confirm the occurrence of the coordination dichotomy in the system. The main center of interactions in the hydroxyl complexes Cu(GluA)(OH)x and MgGluA are oxygens from the carboxyl group. Differences in the coordination mode in the copper(II) and magnesium systems at low pH were observed. Abstract :